Peran Manajemen Sumber Daya Insani Terhadap Kualitas Pelayanan Program Lembaga Sosial Pesantren Tebuireng (LSPT) - Yuni Astriana Khamidah; Isma Nurrokhim; Izzatun Magfirah (Universitas Islam Raden Rahmat, 2026)
Human resource management requires careful handling of the workforce to obtain the best results in achieving organizational goals. Although the number of workers is limited, it does not hinder the organization's ability to provide outstanding services. Even so, the professionalism of employees still needs to be improved in order to comply with the established operational standards, which affects their role as a key element in the organizational structure. With effective management, attentive to employee needs, and careful performance evaluation, organizations can achieve optimal performance and become professional and qualified institutions. The success of an organization's programs largely depends on how human resource management is executed.